Evaluasi Pendahuluan terhadap Aspek Fisik dan Kelembagaan Program Pengembangan Destinasi Percandian Muaro Jambi - CHOIRINNISA, SARAH (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The aim of the research is to conduct an initial evaluation on the physical and institutional aspects of the destination development program of Muaro Jambi temples. The research uses quantitative approach by referring to the concept of tourism destination quality, of tourism organizational competence, and institutional competence indicator. The result of the research shows that Muaro Jambi temples have not been sustained by the availability of adequate amenitas amenity and transportation, even though they have great historical, geological, and agricultural attractiveness. Institutionally, the program becomes the responsibility of tourism organizations in the level of central, provincial, and regency governments with vertical relation mechanism and coordination. However, the condition of tourism-supporting private sectors and the quality of human resources have become challenges for the government to accomplish the vision of Muaro Jambi temples as a world’s tourism destination based on historical site and the center of Buddhism culture in Asia.